Development of an undergraduate antibiotic stewardship training programme for medical students - Bashar, Muhammad Augie (My University, 2022)
Antibiotic resistance is a growing concern because antibiotics are inappropriately overconsumed with few in the development pipeline, leaving prescribers with minimal treatment options. If not addressed, antibiotic resistance could result in prolonged hospital stay, increased mortality and higher healthcare costs. Antibiotic stewardship programmes have been shown to improve prudent antibiotic use. However, most of the antibiotic stewardship programmes are implemented at a postgraduate level with little emphasis given to medical undergraduate students. The World Health Organization highlighted the importance of teaching prudent antibiotic prescribing to undergraduate medical students. This study aimed to develop an educational antibiotic stewardship programme that will assist in teaching medical students in Nigeria and South Africa rational antibiotic prescribing. This study is underpinned by a six-step approach to curriculum development developed by Kern and colleagues. For the purpose of this study, the six-step approach to curriculum development in medical education was modified into two phases. The study was divided into two phases. The emphasis in Phase One was on problem analysis and information gathering, and in Phase Two, an antibiotic stewardship curriculum was developed. In Phase One, three studies were conducted – a scoping review, a survey, and a summative content analysis of the curricula content of Nigerian and South African medical schools. In Phase Two, one study was conducted – a modified Delphi study. The findings from the three stages of Phase One were triangulated and informed the second phase of the study. Two rounds of the modified Delphi study were conducted in Phase Two, where experts drawn from different disciplines participated in the development of antibiotic stewardship competencies for teaching responsible antibiotic prescribing and therapeutic use to medical students in South African and Nigerian medical schools. The consensus was determined using the median and interquartile range. At the end of the two rounds, 88 of the 105 competencies reviewed by the panellists reached consensus and were categorized into knowledge, attitudes and skills domains. An antibiotic stewardship curriculum is designed to be taught in a spiral curriculum over three years using the principle of constructive alignment.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2022